Faktor yang Mempengaruhi Preferensi Makanan pada Mahasiswa Fakultas Kesehatan Masyarakat, Universitas Andalas - Nur, Nadia Chalida; Lova, Luvia Milda; Symond, Denas (Jurnal Kesehatan Indonesia, 2024)
A person's food preferences can be influenced by various factors, including individual characteristics, food characteristics, and environmental characteristics. The study conducted aimed to determine the relationship between several factors, such as money allowance, food expenditure, parents' occupation, nutrition knowledge, food availability, and sensory appeal, and the food preferences of students in the Public Health Faculty at Andalas University. This quantitative study used a cross-sectional design. The research was conducted from June to July 2023. The sample consisted of 100 students who were selected using proportional stratified random sampling technique. Data were collected through questionnaires on money allowance, food expenditure, nutritional knowledge, food availability, sensory appeal, and food preferences. The chi-square test was used for data analysis. The study found that money allowance (p-value=0.030), food expenditure (p-value=0.001), and nutrition knowledge (p-value=0.009) were significantly related to students' food preferences. The father’s occupation (p=1,000), mother’s occupation (p=0.549), food availability (p=0,643), and sensory appeal (p=0.643) had no significant relationship with students' food preferences. It is recommended that students consider rational factors when making decisions about their food preferences. Keywords: food expenditure, food preferences, pocket money, sensory appeal.